Anion-induced molecular motion within interlocked structures - Barendt, T (2016)
This thesis describes the construction and exploration of a variety of interlocked structures that exhibit anion-induced molecular motion of their constituent parts. Chapter One provides a brief overview of the field of supramolecular chemistry; in particular anion recognition and the concept of mechanically interlocked molecules and their applications in the fields of nanotechnology. Chapter Two describes the preparation of a series of bistable [2]rotaxanes followed by thorough investigation of their dynamic properties. Specifically, the success of an iodo-triazolium–naphthalene-diimide-based two-station axle component to facilitate halide-stimulated large-amplitude translational motion of the macrocyclic wheel in a [2]rotaxane is demonstrated. Chapter Three expands on the design principles established in the previous chapter with the synthesis of exotic higher-order structures including the first halogen bonding [3]rotaxane. These systems are capable of the recognition and colorimetric sensing of oxoanions via a novel dynamic pincer-like motion of the macrocycle components. Chapter Four further highlights the capabilities of controlled co-conformational switching in interlocked structures, resulting in a unique mechanism to accomplish anion sensing. The incorporation of C60 fullerene- and ferrocenyl-reporter groups into a four-station [3]rotaxane enables sensing of chloride to be realised by a dual fluorescence response. Chapter Five presents the synthesis of novel interlocked structures containing a substituted perylene diimide motif that functions as a recognition site for macrocycles. Chloride binding stimulates translational motion in a [3]rotaxane and unprecedented rotary motion in a [3]catenane, with co-conformational changes in both systems resulting in a colorimetric response for this anion. Chapter Six describes experimental procedures used throughout this work and details the characterisation of novel compounds. Chapter Seven provides a summary of the major conclusions from the research described in this thesis. .